Assessment of nutritional status, physical activity and behavior towards whole grain consumption among overweight and obese working adults in Kota Bharu Kelantan. - Hanafi, Nur Haziqah (Universiti Sains Malaysia, 2016)
Assessment of nutritional status, physical activity and behavior towards whole grains consumption was carried out on 104 overweight and obese office workers by using a cross sectional study at ten government offices in Kota Bharu, Kelantan. Data was collected using questionnaire encompassing socio-demographic characteristics, behavior towards whole grains, International Physical Activity Questionnaire (IPAQ), and 24 hour dietary recall. Body Mass Index and waist circumference, were measured in order to assess their nutritional status. Majority of respondents was 45 years and 64.4% were females. The mean weight and BMI were 76.98±9.92kg, and 30.77±3.80kg/m2, respectively. The prevalence of overweight and obesity were 56.2% and 53.8% respectively. High risk of abdominal obesity and body fat percentage were 77.9% and 81.7% respectively. A total of 29.8% of respondents had low physical activity level, while 56.7% and 13.5% were in moderate and high physical activity categories respectively. The mean calorie intake of respondent was 1814 ± 674.6 kcal, with 55% from carbohydrate, 14% from protein intake and 31% from fat. The mean of daily consumption of whole grain in a week and serving size of respondent were 2.37±1.71 and 4.64± 2.73 respectively. Majority of respondents have (68.3%) of positive behavior towards whole grain and 78.8% have neutral perception towards whole grain. Significant linear relationship was found between age (b=-0.1, 95% CI=-0.17,-0.02, P<0.05) and energy intake (b-0.002, 95%CI-0.00, 0.003, p<0.05) with BMI, number of children (b=-0.015, CI—0.057, 0.028 P<0.05) with waist circumference and fat intake (b=0.000, 95% CI—0.000, 0.000 P<0.05) with percentage of body fat.